2014
DOI: 10.1108/apjml-09-2014-0141
|View full text |Cite
|
Sign up to set email alerts
|

Moderating role of religious beliefs on attitudes towards charities and motivation to donate

Abstract: Teah, M. and Lwin, M. and Cheah, I. 2014. Moderating role of religious beliefs on attitudes towards charities and motivation to donate. Asia Pacific Journal of Marketing and Logistics. 26 (5): pp. 738-760. 1 Moderating Role of Religious Beliefs on Attitudes towards Charities and Motivation to Donate PurposeThe study aims to examine the relationship between image of charitable organizations, attitudes towards charities and motivation to donate. In addition, the study will investigate the moderating effects of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 85 publications
(169 reference statements)
1
39
0
5
Order By: Relevance
“…However, Ibrahim Sulaiman (2013) found the opposite when religiosity does not influence donation behaviour in Saudi Arabia. While Teah, Lwin and Cheah (2014) found that religiosity is a moderating factor between attitude towards donation and motivation to donate. Apart from that, Amirul Faiz Osman (2015) who done research on the behaviour of cash waqf contribution found the weak effect of religiosity in influencing intention towards cash waqf when the significant level is only at 10 percent degree of significant.…”
Section: Religiositymentioning
confidence: 88%
“…However, Ibrahim Sulaiman (2013) found the opposite when religiosity does not influence donation behaviour in Saudi Arabia. While Teah, Lwin and Cheah (2014) found that religiosity is a moderating factor between attitude towards donation and motivation to donate. Apart from that, Amirul Faiz Osman (2015) who done research on the behaviour of cash waqf contribution found the weak effect of religiosity in influencing intention towards cash waqf when the significant level is only at 10 percent degree of significant.…”
Section: Religiositymentioning
confidence: 88%
“…The citizen with strong religious believes that donation to international charities can help them to gain recognition from employers and co-workers (Teah et al, 2014). The religiosity and materialism were inversely related, whereby religious people tend to become less materialistic (Bakar et al, 2013).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The culture of Malaysian society that tends to have strong religious values proves to have a positive impact on individual tax compliance. Research on motivation to donate in Kuala Lumpur Malaysia found religious belief was a moderator that strengthens motivation to donate (Teah, Lwin, & Cheah, 2014). The reason because it is essential for individuals with strong religious belief to provide a signal in the form of action, where the action is in line with the religious doctrine that they believe.…”
Section: Individual Satisfaction and Tax Moralementioning
confidence: 99%
“…This result is also ongoing with Ibrahim, Musah & Abdul-Hanan (2015) that trust in government is a crucial factor that drives tax morale. The research (Teah, Lwin & Cheah, 2014) on donor institutional confidence, also proves that donating venues affect motivation to donate. Individual trust in international charity is higher than local charity because international charity is considered more efficient and better in distributing funds for the needy.…”
Section: Trust To Government Institutional Individual Satisfaction mentioning
confidence: 99%